2004
DOI: 10.1089/jwh.2004.13.986
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Women's Health Initiative on Hormone Replacement Therapy in a Medicaid Program

Abstract: The WHI influenced all types of HRT use among postmenopausal women in a Medicaid program. Administrative claims data can be a useful tool for monitoring an immediate impact of national guidelines or a national level outcomes trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 9 publications
3
14
1
Order By: Relevance
“…Hersh et al showed a 37% decrease of HRT prescriptions in 2003 compared with 1999 but in another study in a lower educated population (Medicaid program) the decline was less pronounced [19]. In a survey among HRT-users in New Zealand 40% stopped the use of HRT [20]. Our results .…”
Section: Resultscontrasting
confidence: 40%
“…Hersh et al showed a 37% decrease of HRT prescriptions in 2003 compared with 1999 but in another study in a lower educated population (Medicaid program) the decline was less pronounced [19]. In a survey among HRT-users in New Zealand 40% stopped the use of HRT [20]. Our results .…”
Section: Resultscontrasting
confidence: 40%
“…As expected, a reduction in HT use after the WHI publication was reported in a few studies. [6][7][8][9][10][11] Our study findings showed no apparent changes in overall AOM prevalence, reduction in LEE ET AL. 158 estrogen use, and increases in nonestrogen type AOM, suggesting a potential switch from estrogen to nonestrogen type AOM modalities, although we did not evaluate the switching issue on an individual prescription level.…”
Section: Discussionmentioning
confidence: 84%
“…6 As the study focused only on the antiresorptive properties of estrogens in HT formulations, we excluded drug entities containing only progesterone as a single agent and combination products of progesterone without estrogens. We included alendronate, risedronate, etidronate, pamidronate, tiludronate, and zoledronate as bisphosphonates.…”
Section: Target Drugs and Prevalence Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for synthetic progestogens with favorable risk-benefit profiles is an area of intense pharmaceutical activity (Williams and Sigler, 1998;Sitruk-Ware, 2004;Turgeon et al, 2004;Rossouw et al, 2002;Anderson et al, 2004). Nevertheless under these circumstances, millions of women globally have decided to discontinue drugs containing synthetic sex steroids (Hillman et al, 2004;McIntosh and Blalock, 2005). Health care professionals are considering (North American Menopause Society, 2004;Krebs et al, 2004), and many women have elected to use botanical alternatives for hormone replacement therapy (HRT) (Beck et al, 2005).…”
Section: Introductionmentioning
confidence: 99%